1998
DOI: 10.1021/ja973080o
|View full text |Cite
|
Sign up to set email alerts
|

Unified Mechanistic Framework for the Fe(II)-Induced Cleavage of Qinghaosu and Derivatives/Analogues. The First Spin-Trapping Evidence for the Previously Postulated Secondary C-4 Radical

Abstract: Qinghaosu and derivatives were easily reduced by ferrous sulfate in aqueous acetonitrile to give results different from those reported for other reducing systems. The unstable epoxide 7, a compound that was postulated earlier as a species responsible for the antimalarial activity, now has been isolated and characterized. The earlier speculative secondary C-4 radical has also been trapped with 2-methyl-2-nitrosopropane and thus provides the very first direct evidence for the involvement of radicals in the in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
179
3
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(204 citation statements)
references
References 15 publications
13
179
3
5
Order By: Relevance
“…The mechanism of action of artemisinin derivatives is thought to involve the interac-tion between the drugs and hemin within the digestive vacuole of the parasite. [45][46][47][48] The iron-dependent decomposition of artemisinin generates free oxygen radicals that destroy the parasites. The 4-aminoquinolines and aminoalcohols also concentrate within the digestive vacuole but their precise mode of action has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of artemisinin derivatives is thought to involve the interac-tion between the drugs and hemin within the digestive vacuole of the parasite. [45][46][47][48] The iron-dependent decomposition of artemisinin generates free oxygen radicals that destroy the parasites. The 4-aminoquinolines and aminoalcohols also concentrate within the digestive vacuole but their precise mode of action has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…For exploring the mode of action, reaction of QHS and Fe 2+ was carefully studied by Chinese chemists [22,23] . The major products tetrahydrofuran 3 and 3-hydroxy deoxyqinghaosu 4 were proposed to be derived from primary C-centered free radical 1 and secondary C-centered free radical 2, respectively, as shown in Scheme 2.…”
mentioning
confidence: 99%
“…The major products tetrahydrofuran 3 and 3-hydroxy deoxyqinghaosu 4 were proposed to be derived from primary C-centered free radical 1 and secondary C-centered free radical 2, respectively, as shown in Scheme 2. In addition, the electron spin resonance (ESR) signals of the C-centered free radicals were detected [23,24] .…”
mentioning
confidence: 99%
“…12,13 Recently, Gu et al 14 in a DFT study showed that the rate constant for the classical 1,5-H shift is 30 K, respectively, and they reported that the C-centered radical is 5.2 kcal/mol more stable than the O-centered radical. Since there is experimental evidence both for the formation of a secondary 4-C radical and of an unstable epoxide by Wu et al 15 and for the formation of a primary4-C radical, 16 their structures were used in Scheme 1. The epoxide was characterized by its IR spectrum giving rise to ν(OH) and ν (C=O) at 3500 and 1728 cm -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%